2022
DOI: 10.3389/fmed.2022.770184
|View full text |Cite
|
Sign up to set email alerts
|

Association Between White Matter Hyperintensities and Chronic Kidney Disease: A Systematic Review and Meta-Analysis

Abstract: ObjectivesPrevious studies of the associations between white matter hyperintensities (WMH) and chronic kidney disease (CKD) were still conflicting; therefore, our study aimed to conduct a systematic review of all of the available research on this topic and a meta-analysis of the association between WMH and CKD among observational studies.Setting and DesignSystematic review and meta-analysis.Outcome MeasuresSeverity of WMH.Methods and ParticipantsAll relevant studies in public databases were examined until 15 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Pre-treatment morbidity includes cerebrovascular changes, atherosclerosis and hypertension. [18][19][20] Posttreatment complications include a higher risk of hemorrhage and higher all-cause mortality. 1,17 The kidney and the brain have been hypothesized to share a common pattern of microvascular impairment resulting from cardiovascular risk factors, due to their shared status as high-flow end organs with autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment morbidity includes cerebrovascular changes, atherosclerosis and hypertension. [18][19][20] Posttreatment complications include a higher risk of hemorrhage and higher all-cause mortality. 1,17 The kidney and the brain have been hypothesized to share a common pattern of microvascular impairment resulting from cardiovascular risk factors, due to their shared status as high-flow end organs with autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Linked to cerebral small vessel disease, WMHs have been associated with an increased risk of cognitive dysfunction and all-cause dementia [ 31 ], probably by disrupting the connections between the cortex and the subcortical nuclei [ 32 , 33 ] or contributing to the accumulation of amyloid-β proteins [ 34 ]. On the other hand, the relationship between GFR and concluded that CKD is associated with poorer WMHs [ 25 , 35 , 36 ], with mechanisms related to cerebrovascular disease, systemic inflammation, cerebral hypoperfusion, oxidative stress, disturbances of small blood vessels, breakdown of the blood-brain barrier, glial activation, loss of oligodendrocytes, and demyelination caused by chronic diffuse hypoperfusion [ 37–39 ].…”
Section: Discussionmentioning
confidence: 99%